Turizme dayalı büyüme hipotezinin Kuzey Kıbrıs Türk Cumhuriyeti için geçerliliğinin analizi - (:unkn) unknown (My University, 2012)
Turizm bir ülkenin ekonomik, sosyal ve kültürel alanlarda kazanım elde etmesini sağlayan önemli hizmet sektörlerinden biridir. Bu nedenle özellikle turizm ve büyüme arasındaki ilişki araştırmacılar için önemli bir araştırma konusu olmuştur. Bu çalışmada turizm sektörünün ekonomik büyüme üzerinde etkili olacağı tezini savunan turizme dayalı büyüme hipotezi araştırılmaktadır. Turizme dayalı büyüme hipotezinde turizmdeki gelişmenin uzun dönemde ekonomik büyümenin önemli belirleyicisi olduğuna ilişkin nedenler ileri sürülmektedir. Bu hipotezin Kuzey Kıbrıs Türk Cumhuriyeti için geçerli olup olmadığı, 1977-2008 dönemi verileri kullanarak Sınır Testi ve Toda – Yamamoto Nedensellik testi ile incelenmektedir. Elde edilen bulgular Kuzey Kıbrıs Türk Cumhuriyeti için turizme dayalı büyüme hipotezinin geçerli olmadığını göstermektedir.

Tourism is one of the important service sectors of a country, enabling it to earn the gain in economic, social and cultural fields. For this reason, especially the relationship between tourism and the growth has been an important research area for researchers. In this study, the tourism-led growth hypothesis, which defense the thesis of tourism sector’s impact on economic growth, will be under investigation. In tourism-led growth hypothesis are given reasons that tourism development is important determinant for the long-term economic growth. This study is examining whether this hypothesis is valid for the Turkish Republic of Northern Cyprus or not, by using data over the period 1977-2008 through the bounds test and the Toda- Yamamoto causality test. The results obtained show that the tourism-led growth hypothesis is not valid for the Turkish Republic of Northern Cyprus.
The analysis of tourism led growth hypothesis’s validity in the Turkish republic of northern cyprus